KONTEN TIKTOK #EvaClassroom TERHADAP PENGEMBANGAN DIRI FOLLOWERS: STUDI KUANTITATIF PADA PENGIKUT @aliciaeva9 - Ginandita Novi Andhini; Hudi Santoso; Enden Darjatul Ulya; Fahmi Fuad Cholagi (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2026)
We Are Social & Meltwater (July 2025) reported that TikTok users in Indonesia reached 194.37 million. One creator who utilizes it as an educational tool is Eva Alicia through her #EvaClassroom segment, which focuses on self-development topics. This study aims to determine the content and delivery of #EvaClassroom content, while also examining its influence on followers' self-development in terms of growth mindset. The study used a quantitative explanatory approach with the S-O-R (Stimulus-Organism-Response) theory. A total of 100 respondents were selected through purposive sampling from followers of the TikTok account @aliciaeva9. The results showed that #EvaClassroom content had a significant and positive effect on followers' self-development, with a model contribution of R² = 0.668. This finding confirms that TikTok functions not only as an entertainment medium but also as an effective non-formal educational medium for supporting the self-development of the younger generation. Keywords: #EvaClassroom, Growth Mindset, Educational Media, Self-Development Content, TikTok